VEGFA GENE POLYMORPHISM (С-2578A, C+936T) IN PATIENTS WITH BREAST CANCER - A. V. Shevchenko; V. I. Konenkov; O. V. Golovanova; A. E. Blagodatskikh; E. Yu. Garbukov; M. N. Stakheeva (Медицинская иммунология, 2014)
Abstract. Angiogenesis plays the major role in growth, progression and metastasis of different solid umors. Vascular endothelium growth factor (VEGF) is a basic factor of angiogenesis regulation. The aim of present study was to evaluate possible correlations between C-2578A and C+936T VEGFА gene functional polymorphisms, and risk of breast cancer development. An association of -2578AA and -2578СС /+936СС VEGFA polymorphisms with incidence of breast cancer was revealed in our study. Distinct features of VEGFA genotype distribution were found for women with lymphogenic metastases and differences in menstrual status.